2011
DOI: 10.1142/s0192415x1100924x
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Therapy in Dialysis Patients — A Randomized Trial

Abstract: The aim of this study is to evaluate the effects of far-infrared (FIR) rays on the meridian in hemodialysis (HD) patients. End-stage renal disease or kidney failure is the last stage of chronic renal failure, and often implies that the renal function cannot be restored and HD or kidney transplantation is required as a life-saving measure. HD patients often feel sick, debilitated, demotivated, and sad. A quasi-experimental design was conducted using convenience sampling with 61 HD patients from a hemodialysis c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…Shipley et al followed their patients for six months in a case series of 20 patients – no control group - and reported maturation in 10 of those patients [40]. Two studies did not report on the outcomes of interest to the author of this systematic review [29], [41].…”
Section: Resultsmentioning
confidence: 99%
“…Shipley et al followed their patients for six months in a case series of 20 patients – no control group - and reported maturation in 10 of those patients [40]. Two studies did not report on the outcomes of interest to the author of this systematic review [29], [41].…”
Section: Resultsmentioning
confidence: 99%
“…Thermal therapy through acupoints to restore the balance between Yin and Yang has been shown to improve vitality in patients with HD. 35 There is also evidence that the use of Tianjiu on the Lung-Qi tonifying acupoints such as BL12 (Fengmen), BL13 (Feishu) and GV14 (Dazhui) can reduce the symptoms of allergic rhinitis and regulate the autonomous nervous system in patients with asthma. 36 37 On the basis of our experience in clinical practice, Tianjiu therapy with pasting on acupoints to activate Yang-Qi could reduce the fatigue of patients with HD.…”
Section: Discussionmentioning
confidence: 99%
“…We found significant differences in the MEC values between the unaffected and affected sides of patients with acute ischemic stroke. Some interference factors, such as age, sex, underlying disease, body fat, weather, and humidity, may affect the MEC values [12, 27, 28, 3436]. Xie measured the MEC values of twelve meridians of healthy people, and the results showed that the MEC values of males were higher than those of females [37].…”
Section: Discussionmentioning
confidence: 99%